2002
DOI: 10.1590/s1516-35982002000600014
|View full text |Cite
|
Sign up to set email alerts
|

Determinação de Níveis de Metionina+Cistina para Poedeiras Semi-pesadas Alimentadas com Rações contendo Levedura Seca (Saccharomyces cerevisiae)

Abstract: RESUMO -Um experimento foi realizado utilizando-se 120 galinhas poedeiras de ovos marrons, da linhagem comercial Isa Brown, alimentadas com rações contendo levedura de cana-de-açúcar, visando à determinação das exigências nutricionais de metionina+cistina (met+cis). As aves possuíam 51 semanas de idade ao início do experimento, que teve a duração de 84 dias, com três períodos de 28 dias cada. O delineamento experimental utilizado foi o de blocos casualizados com cinco tratamentos e quatro repetições. Os tratam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1
16

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 11 publications
(12 reference statements)
4
12
1
16
Order By: Relevance
“…Table 3 -Mean (± standard error) feed intake (g/bird d) and the egg production (%) from 33 to 48 weeks in response to methionine + cystine (met+cys) intake The effect of met+cys intake on the feed conversion per mass (P<0.001) was also observed in other studies (Togashi et al, 2002;Jordão Filho et al, 2006;Safaa et al, 2008). This variable depends on feed intake and egg production, which was influenced by the different met+cys intakes (Togashi et al, 2002). In contrast to the results of this study, some authors observed no significant differences in this variable (Pavan et al, 2005).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Table 3 -Mean (± standard error) feed intake (g/bird d) and the egg production (%) from 33 to 48 weeks in response to methionine + cystine (met+cys) intake The effect of met+cys intake on the feed conversion per mass (P<0.001) was also observed in other studies (Togashi et al, 2002;Jordão Filho et al, 2006;Safaa et al, 2008). This variable depends on feed intake and egg production, which was influenced by the different met+cys intakes (Togashi et al, 2002). In contrast to the results of this study, some authors observed no significant differences in this variable (Pavan et al, 2005).…”
Section: Resultssupporting
confidence: 67%
“…This increase may be due to an increase in the maintenance requirement as a function of the age of the bird estimated by the BL model as 37, 39, 48 and 52 mg/bird d for the first, second, third and fourth periods, respectively, considering that this model describes the individual response well. The optimal digestible met+cys intake for the four periods was high compared with those reported in the literature (Togashi et al, 2002;Sá et al, 2007;Barbosa et al, 2010). The difference in those results is related to the type of methodology, and the analysis in the current study was used for each period and not for the overall study period.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…O resultado encontrado neste trabalho diverge do obtido por Togashi et al (2002), que observaram estimativa de 0,57% de M+C total em poedeiras de 51 semanas de idade alimentadas com dietas à base de milho, farelo de soja e levedura, provavelmente porque as aves estavam em idade avançada, apresentando, portanto, exigência específica, ou por causa das diferenças no teor protéico da ração utilizada pelos autores (13%PB). (Soybean meal) 19,96 Glúten de milho (Corn gluten) 4,20 Calcário (Limestone) 9,94 Fosfato bicálcico (Dicalcium phosphate) 1,51 Amido (Starch) 0,78 DL-metionina (DL-methionine) 0,02 L-lisina·HCl (L-lysine HCl) 0,27 Cloreto de colina (70%) (C. chloride) 0,20 Óleo vegetal (Vegetable oil) 0,45 Sal comum (Salt) 0 Composição química…”
Section: Resultsunclassified
“…A formulação de rações com milho e farelo de soja não atende completamente às exigências em metionina e lisina, tornando necessária a utilização de fontes industriais destes aminoácidos para suprir estas deficiências (Togashi et al, 2002), aumentando a eficiência de utilização da proteína dietética.…”
Section: Introductionunclassified